SUPEROXIDE DISMUTASE LOADED NIOSOMES DELIVERY TO HAIR FOLLICLES: PERMEATION THROUGH SYNTHETIC MEMBRANE AND GUINEA PIG SKIN - KARAMI, MASOUD ALI; JALILI RAD, MARZIE; ZADEH, BEHZAD SHARIF MAKHMAL; SALIMI, ANAYATOLLAH (International Journal of Applied Pharmaceutics, 2019)
Objective: Alopecia aretea is associated with an increase in free radicals causing damage to hair follicles. Superoxide dismutase (SOD) with sufficient penetration through hair follicles, can prevent their death by its strong antioxidant effects. SOD with high molecular weight underwent limitation in follicular delivery. The aim of this study was the improvement of SOD localization into hair follicles. Methods: SOD-loaded niosomes were prepared by thin layer hydration method and were used as a vehicle for delivery to hair follicles through guinea pig skin and the synthetic membrane. Particle size, entrapment efficiency, drug release, and permeability parameters through hairly and non-hairly pig skin compared with a synthetic membrane were evaluated. Results: Niosomes demonstrated 152-325 nm particle size and the SOD burst and sustained release from niosomes were mainly controlled by diffusion and dissolution phenomena. SOD was protected against degradation by niosomes and after six months, enzyme content and activity decreased less than 5%. In comparison with free SOD, niosomes increased SOD affinity to penetration through follicles by interaction with sebum. Likewise, niosome's characters such as type of surfactant, solid lipid/liquid lipid ratio played critical roles on SOD deposition on hair follicles. Conclusion: Synthetic membrane and hairy guinea pig skin demonstrated similar barrier property against free-SOD thereby implying that free SOD does not interact with guinea pig sebum. Niosomes can introduce a suitable carrier for SOD localization into the hair follicles.